Input-Output Linkages and Monopolistic Competition: Input Distortion and Optimal Policies - Benjamin Jung; Wilhelm Kohler (ZBW - Leibniz Information Centre for Economics, 2020)
We show that the combination of monopolistic competition and input-output linkages generate what we call an input distortion. The distortion arises because material input prices involve a markup over the social opportunity cost. This has so far escaped attention in the literature addressing efficiency of monopolistic competition equilibria. Using a stylized single sector model, we provide a full description of the social optimum for an economy featuring an input-output linkage in the presence of monopolistic competition. Using this as a benchmark, we describe the allocational inefficiency of a decentralized market equilibrium as well as first-best policies to achieve efficiency. In an integrated world equilibrium, a material input subsidy and an output subsidy turn out to be perfect substitutes. A wage tax is unable to serve in offsetting the input distortion. In a cooperative policy setting with two countries, an input subsidy is a second-best policy to address the input distortion.
Keywords: F12; 330; input-output linkages; monopolistic competition; international trade; allocational inefficiency; optimal policy